Dormant tumour cells, their niches and the influence of immunity. Issue 11 (November 2018) - Goddard, Erica; Bozic, Ivana; Riddell, Stanley; Ghajar, Cyrus
Abstract Despite increased focus on the clinical relevance of dormant metastatic disease, our understanding of dormant niches, mechanisms underlying emergence from dormancy, and the immune system's role in this phenomenon, remains in its infancy. Here, we discuss key work that has shaped our current understanding of these topics. Because tumour dormancy provides a unique therapeutic window to prevent metastatic disease, we discuss on-going clinical trials and weigh the potential for immunotherapy to eradicate dormant disease. Goddard et al review recent advances in our understanding of dormant tumour cells, highlight their cross-talk with immune responses, and elaborate therapeutic implications to treat metastatic malignancies.